Multimedia Dalam Bahan Pengajaran Pembelajaran Berbantukan Komputer - Azmi, Mat Safar (2000)
This project consists of two sections. The first section deals with the development of the computer aided instruction courseware prototype for learning and teaching fractions in the subject of Mathematics to form one students. The second section concentrate on the study being carried out on the courseware in an effort to determine its suitability for usage to students and teachers. The result of the study shows that the courseware is suitable for learning fractions to form one students. This MASKOM model courseware prototype is able to assist teachers as supporting materials in the teaching of the topic mentioned. However, the quality of this courseware prototype can be further upgraded. For example, the element of sound effects can be added to capture the students interest in using this courseware prototype as one of the teaching aids in learning and teaching Mathematics especially for the topic of fractions to form one students.